Elbow rehabilitation using intelligent medical devices (Balneo and PRM Research Journal, 2021)
The purpose of this paper is to demonstrate that the process of elbow joint rehabilitation can be monitored and improved usingintelligent medical devices. During the study, an orthosis-type medical device was developed that monitors the mobility of theelbow joint in case of pathology. This device is useful in monitoring flexion movements (forward and backward), as well asinternal and external rotation. For this purpose, a set of sensors were used that will capture the necessary and specificinformation, and the extracted data will be transmitted to a microcontroller for processing. The orthosis is one that can becustomized according to the patient's pathology because it will analyse the data collected and interpret the values according to thecalibration performed on the patient. The orthosis can be used both in the evaluation of joint dysfunctions at the elbow and in arehabilitation program to avoid vicious positions. The positioning of the orthosis will be done together with the specialist doctoror in the presence of a physiotherapist, following the detailed clinical examination, so that the calibration of the sensors can beperformed correctly. The device can emit warning sequences that will depend on the movements that the patient will perform,movements that can be sudden or accidental.
Keywords: elbow joint; orthesis; physiokinetotherapist; rehabilitation; health improvement